Review of Radiation Dose Metric Tracking for Patients: Ethical Implications of the “Do Not Disclose” Standard - Brunger, Fern; Kendall, Edward (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2024)
Medical diagnostic imaging tests that produce ionizing radiation now deploy technology that captures an individual patient’s cumulative radiation dose. This raises the question of whether there is an imperative for regional health authorities to disclose this information to physicians who may then engage their patients in decisions about whether the potential harms are worth the benefits of subsequent diagnostic imaging. Currently, the advice of the professional bodies providing standards of practice for medical diagnostic imaging is to withhold this information from physicians. Their concern is that cumulative dose information is difficult to evaluate in terms of risk to individual patients; it is not easily applicable to clinical decision making about the appropriateness of a subsequent imaging exam; and referring clinicians will feel compelled to offer a patient a less efficacious non-ionizing test, which could negatively affect patient care. We present a critical analysis of several assumptions underlying the stance of non-disclosure. Working at the intersection of medical physics, medical anthropology, and clinical ethics, we offer an alternative framing of the discourse of risk that has shaped the recent scholarly debate on disclosure of individual cumulative radiation dose. We posit that a persuasive argument can be made against the stance of the professional bodies and for a policy of disclosure – provided that such a policy prioritizes patient-centred shared decision making, radiologists as risk-interpretation experts, and the authority of the prescribing physician.